AB0384 Rheumatic arthritis patients with very high cardiovascular risk: poor results in changes in lifestyle during follow-up. (12th June 2018) - Vegas-Revenga, N.; Portilla, V.; Domínguez-Casas, L.C.; Martín-Varillas, J.L.; Atienza-Mateo, B.; Agudo, M.; Rueda-Gotor, J.; Hernández, J.L.; Blanco, R.; González-Gay, M.A.; Corrales, A.
Abstract : Background: Rheumatoid arthritis (RA) is associated with accelerated atherosclerosis, which results in high cardiovascular morbidity and mortality. The European Atherosclerosis Society recommends a strict control of cardiovascular (CV) risk factors, focusing in a healthy lifestyle, for the prevention of future CV events. Objectives: Our aim was to assess the characteristics of healthy lifestyle in patients with RA and very high risk of CV events. Methods: Prospective study that included a group of 113 patients, of whom 65 presented carotid plaques on carotid ultrasound study and, due to this, were categorised as having very CV high risk at the baseline visit. At this time, patients were informed about the risks associated to their disease and the high risk of having CV events. They were even warned of the need of healthy lifestyle habits. Data on lifestyle, smoking, obesity and diabetes mellitus were collected at baseline and last visit (with an interval of more than 5 years) Results: The results of the 65 patients at the last visit are shown in table 1 . The average age was of 67 years, with a disease duration of 17 years and high prevalence of dyslipidemia (72%), HTA (62%) and obesity (40%). Data obtained at the basal and last visit (with an average difference of 5.5 years) were compared in table 2. At last follow-up none of the smokers at baseline had discontinued smoking. There were no significant differences in the body mass index (BMI) average. Nevertheless, there was increase in the number of patients with a BMI <30 (36% vs 31%). Only a few patients claimed to go on any type of diet (20%), although the majority (88%) had classic CV risk factors (DM, HTA, obesity or dyslipidemia) at baseline that required adequate diet regime. Yet, more than half of the patients (62%) made regular exercise (>3 times/week) and did not have a sedentary lifestyle (50%), despite having a mean age of 67 years and long disease duration at baseline. Poor control of diabetes mellitus (DM), was found in more than half of the patients. Conclusions: Despite having been informed on the high risk of CV events, patients with RA included in the category of very high CV risk performed poor long-term control of factors that include a healthy lifestyle. Disclosure of Interest: None declared